FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR SISWA SD NEGERI 010 SIARANG-ARANG KECAMATAN PUJUD TAHUN PELAJARAN 2013/2014 - Sulastri '; Rosmawati '; Abu Asyari Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Absrtact : This studyentitled: Factors Contributing toStudentLearning DifficultiesSDN010-charcoal rerunningPujudRokan Hilirin the school year2013/2014"The formulation of this study were1) Howgeneral descriptionof external factorsthatcauselearning difficultiesfourth gradestudentsN010rerunning-charcoal, PujudRokan Hilir2013/2014school year. 2) How doesa general overviewInternalfactorsthatcauselearning difficultiesfourth gradestudentsrerunningN010-charcoal PujudRokan Hiliracademic year2013/2014. 3) External factorsaredominantfacedbyfourth grade studentswhohave difficulty learninginelementary schoolN010-charcoal rerunningPujudRokan Hiliracademic year2013/2014. 4) The internal factorsaredominantin the face byfourth grade studentswhohave difficulty learninginelementary schoolN010-charcoal rerunningPujudRokan Hiliracademic year2013/2014. 5) What factorsaremoredominantof the twogroups offactors thatlead tolearning difficultiesin thefourth gradestudentrerunningN010-charcoal PujudRokan Hiliracademic year2013/2014. The purposeof thisstudywas to determine theexternal factorsthatcauselearning difficultiesSDN010PujudRokan Hiliracademic year2013/2014. In accordancewith theobjectivesof the study,themethodusedinthisresearchisdescriptiveanalyticmethod, which is a methodof researchthataims to determinethe value ofan independentvariablebothindependent variablesbetweenvariableswith one another. Iesymptomsthataffectstudentlearning difficultiesfacedfourth gradeN-010 rerunningPujudcharcoal. The data usedinthisresearchisthe dataabout the factorsthatcauselearning difficultiesfaced bystudentsfourth gradeN-010 rerunningcharcoalPujudinstrumentusedin the form ofa questionnaire. The findingsof this studyindicatethat based onpreliminaryanalysisofeach variableisa descriptivestudyof the factorsthatcauselearning difficulties. Based on thediscussion, it canbe concludedthat, description of the factorsof student learningdifficultiesSDN010-charcoal Pujudrerunningboth internal and external, including themedium category. As arecommendationtodo thatinthisstudyisthatthefamilyisthe parentsin order tobe able totake stepsto reduce factorsthatlead tostudent learningdifficultiesat home. Toaddress the factorsthatlead tostudent learningdifficulties, especially inschools. To thecounselorat theschool tohelpstudentsovercomelearning difficultiesthat are internaland external. Keywords: Factors Contributing toStudent LearningDifficulties